Economic Incentives in Budgetary Control Systems. - Demski, Joel S.; Feltham, Gerald A. (The Accounting Review, 1978)
This article explores conventional questions of why and how budgets should be employed for motivation purposes in an economic setting. The authors focus on the types of employment contracts that are associated with equilibrium allocations in the labor market. Market incompleteness is a necessary condition for use of budgets in the employment contract. Beyond this, issues of controllability, management by exception, and tightness of standards are observed to depend on the contracting environment faced by the individual agents.